94: HEALTH RELATED QUALITY OF LIFE OF PATIENTS WITH ESOPHAGEAL CANCER FOLLOWING ESOPHAGECTOMY TREATED WITH NEOADJUVANT CHEMORADIOTHERAPY OR CHEMOTHERAPY: A EUROPEAN MULTICENTER STUDY. (23rd April 2022) - Schuring, N; Markar, S; Hagens, E; Jezerskyte, E; Sprangers, M; Johar, A; Gisbertz, S; Van Berge Henegouwen, M
Abstract: Background and aim: Curative treatment for patients with esophageal cancer consists of neoadjuvant treatment followed by an esophagectomy. Different neoadjuvant strategies exist; perioperative chemotherapy (pCT) and neoadjuvant chemoradiotherapy (nCRT). Both strategies improve the 5-year overall survival rate, however, whether differences exist in long-term health related Quality of Life (HR-QoL) has not been studied. The aim of this study is to compare HR-QoL between perioperative chemotherapy and neoadjuvant chemoradiotherapy in esophagectomy for cancer patients. Methods: Disease-free patients following esophagectomy for cancer in one of the participating LASER study centers between 2010 and 2016, following neoadjuvant treatment with chemoradiotherapy or chemotherapy, were extracted for analysis from the LASER study database. Included patients completed the LASER, EORTC-QLQ-C30 and QLQ-OG25 questionnaires at least one year following surgery. Primary outcome was to assess long-term HR-QoL between patients treated with pCT or nCRT, using univariable and multivariable logistic regression analysis. Results: Among the 565 included patients, 349 (61.8%) received neoadjuvant chemoradiotherapy, and 216 (38.2%) patient were perioperatively treated with chemotherapy. The mean age was 63.7 years (± SD 8.6) with a mean time since surgery of 4.3 (± 1.7) years. After multivariable analysis patients treated with pCT reported worse outcomes on the 'Social Functioning' domain (∆means 4.56 P -value<0.05) and more symptomatology on the domains 'Insomnia' (∆means 5.65 P -value<0.05) and 'Diarrhea' (∆means 5.93 P -value<0.05) of the QLQ-C30, and more symptomatology on the domains 'Reflux' (∆means 7.40 P -value<0.05), 'Odynophagia'(∆means 4.66 P -value<0.05) and 'Pain and discomfort'(∆means 4.34 P -value<0.05) of the QLQ-OG25. No statistically significant differences were observed for the LASER key symptoms. None of the observed differences in mean scores of HR-QoL domains were clinically relevant (∆means≠ ≥ 10 points). Conclusion: Some differences in favor of nCRT were observed in long-term HR-QoL domains for patients following esophagectomy for cancer. However, none of the observed differences was clinically relevant (∆means≠ ≥ 10 points). HR-QoL is unhelpful when deciding on neoadjuvant strategy.